Evidences of Tsunami dépositifs along the moroccan Atlantic Caost ( Tangier -Asilah ) : Methidological approch, Sites analysis and hazard - El Talibi Hajar (Université AbdelMalek Essaadi, Faculté des Sciences et Techniques, Tanger, 2016)
Despite a position along the passive margin of Africa, the Moroccan Atlantic coast is under the influence of the earthquake generation zone related to the collision between African and European plates along a West-East fault line crossing Gibraltar strait. Throughout history, several quakes triggered tsunamis that struck the shores of Portugal and Spain. Five tectonic sources are still candidate for many events. Southward, the Moroccan coastline was affected by these tsunami waves reaching 2 to 15 m in depth as documented in western historic archives for the cities of Tangier, Asilah, Sale and Mazagao. This thesis project intends to initiate research and recognition in tsunami deposits along the Moroccan Atlantic coast by focusing study on two axis: The first one, consist on Investigating potential sites for the tsunami deposition and conservation, by using the modeling of the tsunami propagation from tsunamigenic potential sources of seismic origin in the Atlantic Ocean. In Fact, numerical simulation of the tsunami from the HSF source allows identifying the most important flooding sites (Tahaddrat estuary and Ain Guemmout Coastal plain), where the inundation limit reaches 2km inland and tsunami deposits were recognized. The second axis is devoted to search and study sedimentary signature of recorded tsunami deposits along the Moroccan Atlantic coast, based on a fine investigation in which traditional methods of field work and sedimentology are coupled with geophysical and geochemical proxies. It aims to identify new tsunamis deposits related to the so-called “1755 Lisbon tsunami” and to provide new insights on the characteristics of this event along the Atlantic Moroccan coasts. The deposits identified, have been deciphered and their characteristics have been used to establish flooding heights, extension of flooded areas and run-up. v In Tahaddart estuary, we found out morphologies and sedimentary deposits evidencing a strong energy-flooding event. This event we attribute to the 1755 tsunami left noticeable traces on a hilly dissected topography. In the proximal domain, no deposits were emplaced. The high turbulence of the flow allows a complete erosion of the soil. Landward, the decreasing of the energy induced a strong depositional process. The thick brownish sandy layer deposited contains at the base large angular rip-up clasts of dark soil. Marine origin of the deposits is attested by the presence of benthic and planctonic foraminifera. In the distal domain, the sudden loss of energy, due i) to a reverse slope ii) and a flow diffluence resulting from the presence of a pass between two dunes, resulted in an accumulation of a huge amount of unsorted marine bioclasts, rounded pebbles, sub-angular beach rock clasts, remains of microlithic industry, and pieces of pottery displaying blunt breaks. Reaching the proximal dune, beyond an undulating line, still perceptible in the landscape, the flow energy was insufficient to erode the soil, which remained unaffected. These new insights plead for a high energy flooding that might be consistent with the waves depth provided by the 1755 archives. Application of the AMS technique to the sediments confirmed that the lower part of deposits was emplaced by a landward flow spreading N91°-171° (uprush phase) while the upper part was oriented seaward N280°-325° with a topographical control (backwash phase). At the very base of the deposit, the first AMS (anisotropy of magnetic susceptibility) measure gives an uprush direction of N105°. In Ain Guemmout coastal plain, the waves had run-up heights more than 9m and deposited shells, sand with lithic clasts and seldom boulders. The heights reached by these waves and the the out-sized boulder transported along shoreline suggest that tsunamis waves rather than storm were the most probable wave form. The sampled stratigraphic sections are composed of upper sand and lower clay units. Typically, these unusual deposits display abrupt sharp basal contact, thinning and finning inland, massive structure and significant lateral variations. Distinction between tsunami and storm deposits was demonstrated by the amalgamation of rip-up clasts exclusively known in the tsunamigenic deposits. vi A multi-proxy approach using sections sediment, textural, morphoscopic, microtextural and micropaleontological analysis on Tahaddart estuary and Ain Guemmout coastal plain provide high-resolution record of a high energy marine flooding. Grain surface microtextural analysis evidenced to be a complementary procedure applied for the identification of extreme marine inundation. Tsunami grains from Tahhadar and Ain Guemmout samples presented a recurrent existence of fresh surfaces and percussion marks once compared with possible source material (Beach, costal dunes and marshlands). The heavy minerals content decreased upward tsunami units and presented resemblances with beach and coastal dune samples. The study of microfossils shows that the species founded in tsunami deposits from Tahaddart and Ain Guemmout are common in marine to brackish-hypersaline environments and consist of mainly shallow water species like Ammonia sp.; Elphidium crispum. These new insights plead for a high energy flooding that might be consistent with the waves depth provided by the 1755 archives.
Keywords: Géologie; Sédimentologie; Tsunami; Sedimentary signature; Anisotropy of magnetic susceptibility; Micropleantology; Quartz microtexture; Tangier; Morocco